COMPARISON OF PHENOL REMOVAL IN ANAEROBIC FLUIDIZED BED REACTORS WITH SAND AND GAC MEDIA - A.R. Yazdanbakhsh; A.R. Mesdaghinia; A. Torabian; M. Shariat (Tehran University of Medical Sciences, 1997)
In this study two identical anaerobic completely mixed fluidized bed reactors with GAC and sand media were employed for COD & phenol removal. At loading rate of 1.6 g phenol L-1d-1, the efficiency of phenol removal in GAC & sand reactors were 97.7% & 74%, respectively. At high loading rate of phenol (6.09 g phenol I: 1d1) the efficiency of phenol removal in GAC reactor was better than 95%. In GAC reactor, the main mechanism for phenol removal at steady state condition was biological process; this was concluded through balance of gas production and COD removal. Better efficiency of GAC reactor comparing with sand reactor was because of resistance to fluctuations, higher surface for biomass growth and adsorption capacity of activated carbon.